Periostin-mediated NOTCH1 activation between tumor cells and HSCs crosstalk promotes liver metastasis of small cell lung cancer - Linlin Lou; Keren Peng; Shumin Ouyang; Wen Ding; Jianshan Mo; Jiayu Yan; Xiaoxiao Gong; Guopin Liu; Jinjian Lu; Peibin Yue; Kai Zhang; Jian Zhang; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Metastasis is the primary cause of mortality in small cell lung cancer (SCLC), with the liver being a predominant site for distal metastasis. Despite this clinical significance, mechanisms underlying the interaction between SCLC and liver microenvironment, fostering metastasis, remain unclear. Methods SCLC patient tissue array, bioinformatics analysis were performed to demonstrate the role of periostin (POSTN) in SCLC progression, metastasis, and prognosis. Cell migration, invasion and sphere formation assay were performed to determine the oncogenic role of POSTN. RNA sequencing analysis was utilized to identify the key signaling pathway regulated by POSTN. Immunoprecipitation, immunofluorescence and co-culture system were used to clarify the mechanism of POSTN-NOTCH1 axis in tumor cells-hepatic stellate cells (HSCs) crosstalk. Subcutaneous xenograft model and liver metastasis model were established to examine the anti-tumor growth and metastases effect of targeting POSTN-NOTCH1 signaling axis. Results Elevated expression of POSTN in SCLC is correlated with accelerated tumor progression and metastasis. Conditioned medium rich in POSTN derived from SCLC tumors demonstrates the ability to activate HSCs in the liver microenvironment. Mechanistically, POSTN emerges as a binding partner for the membrane receptor NOTCH1 and transducing the extracellular signals to intracellular fibroblasts. Furthermore, targeting the POSTN-NOTCH1 signaling axis proves effective in suppressing SCLC tumor growth and inhibiting liver metastasis. This study elucidates that the SCLC-derived secreted protein POSTN interacts with NOTCH1 on HSCs to promote the activation of HSCs, thereby providing a favorable microenvironment for liver metastasis. Conclusion These findings uncover the intricate communications between primary SCLC cells and HSCs in the tumor microenvironment mediated by the secreted protein POSTN in the context of liver metastasis. Consequently, targeting the POSTN-NOTCH1 signaling axis emerges as a promising therapeutic strategy for metastatic SCLC.